Performance characterization and application of composite adsorbent LiCl@ACFF for moisture harvesting - X. Y. Liu (Nature Portfolio, 2021)
Abstract Freshwater scarcity is a global threat to modern era of human society. Sorption-based atmospheric water harvesting (AWH) is prospective to provide fresh water for remote water-stressed areas lacking in water and electricity. Adsorbent material plays a vital role in such AWH systems. Here, we report a solid adsorbent synthesized by impregnating hygroscopic salt lithium chloride (LiCl) into solidified activated carbon fiber felt (ACFF modified by silica sol). Composite samples immersed with different mass concentrations of silica sol are prepared and characterized for dynamic water uptake, equilibrium water uptake, textural and thermal properties. AS5Li30 (ACFF + 5 wt% silica gel + 30 wt% LiCl) exhibits an efficient water uptake of 2.1 g/g at 25 °C and 70% relative humidity (RH). The material further demonstrates a heat storage capacity of 5456 kJ/kg. Its low regeneration temperature (< 80 °C) and good cycle stability make it feasible to be used in practical water production applications, driven by solar energy and other low-grade energy. Estimation results show that water harvesting unit can produce 1.41 gH2O/gAS5Li30 under 25 °C and 75% RH.